Synthesis, physico‐chemical characterization and bioevaluation of Ni(II), Pd(II), and Pt(II) complexes with 1‐(o‐tolyl)biguanide: Antimicrobial and antitumor studies. (28th May 2020) - Nuţă, Ileana; Badea, Mihaela; Chifiriuc, Mariana Carmen; Bleotu, Coralia; Popa, Marcela; Daniliuc, Constantin‐Gabriel; Olar, Rodica
Abstract : New complexes of type [M(tbg)2 ]Cl2 [tbg = 1‐( o ‐tolyl)biguanide; M = Ni(II), Pd(II), and Pt(II)] were synthesized and characterized to develop new biologically active compounds. The features of the complexes were assigned from microanalytical and thermal data. The NMR, FT‐IR, and UV‐Vis spectra were established by comparison with HtbgCl. All complexes exhibit a square‐planar geometry resulting from the chelating behavior of tbg. The HtbgCl and [Ni(tbg)2 ]Cl2 complexes were fully characterized by single‐crystal X‐ray diffraction. The HtbgCl species crystallize in the monoclinic C 2/ c spatial group, while the Ni(II) complex adopts an orthorhombic Pna 21 spatial group. The structure is stabilized by a complex hydrogen bonds network. The in vitro antimicrobial assays revealed improved antimicrobial activity for complexes in comparison with the ligand against both planktonic and biofilm embedded microbial cells. The most efficient compound, showing the largest spectrum of antimicrobial activity, including Gram‐positive and Gram‐negative bacteria, as well as fungal strains, in both planktonic and biofilm growth states was the Pd(II) complex, followed by the Pt(II) complex. The Pt(II) compound exhibited the most significant antiproliferative activity on the human cervical cancer SiHa cell line, inducing a cell cycle arrest in the G2/M phase. Abstract : The synthesis and characterization of new Ni(II), Pd(II), and Pt(II) complexes with 1‐( o ‐tolyl)biguanide are described. The effective antimicrobial activity was evaluated against both Gram‐negative and Gram‐positive bacteria as well as fungal strains in both planktonic and biofilm embedded states while the cytotoxicity was assayed on the human cervical cancer SiHa cell line.